(untitled) (Journal of the College of Basic Education, 2022)
Abstract The present study aimed to investigate the effectiveness of an indicative, cognitive, behavioral and preventive program on reducing the school dropouts and improving the level of achievement among the Syrian refugees in Jordan, and to detect the differences in the level of school dropout and achievement according to the variables of six, grade and social and economic level of the family. The sample consisted of (80) 9th and 10th grade female students of the Syrian refugees. The participants were intentionally selected from abd Latif Abdeen Elementary School for Boys and Qadisiyah Basic School for Girls (Syrian period) in Amman, aged from (15) to (17) years. The participants distributed evenly into two groups: the control group (n = 40) female students were, and the experimental group (n = 40). Pre-post Scale of school dropout utilized for data collection. The students’ scores in Arabic, English, mathematics collected from the International Relief Organization for the academic year 2015/2016 to identify the students’ level of academic achievement. The results showed no statistically significant differences in all dimensions of school dropouts and in the total scale for the experimental group; hence the indicative, cognitive, behavioral and preventive program was effective in reducing the level of school dropout among Syrian refugee female students (the experimental group). The results showed no differences due to the impact of the group in the post-achievement, which shows the ineffectiveness of the program to improve achievement. The results showed that there were no statistically significant differences due to the impact of six and grade upon school dropout and its dimensions and in post-achievement. The results also showed no statistically significant differences on school dropout and its dimensions attributed to the socio-economic level of the family; while the results showed differences in the post-achievement in favor of the middle and high socio-economic level of the family. In light of the study findings, the researcher made a number of educational and research recommendations, which drew the attention of officials at the Ministry of Education and Organization of International Relief to activate the indicative programs, including the cognitive-behavioral one, and provided for students of Syrian refugees in a way for motivating them to pursue studies without discontinuation, and try to conduct similar studies through revealing the impact of cognitive-behavioral program on improving time management skills, organizing school hours, recollection habits and reducing the level of future anxiety; for its impact on improving academic achievement.